2010
DOI: 10.1063/1.3291125
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced high temperature thermoelectric characteristics of transition metals doped Ca3Co4O9+δ by cold high-pressure fabrication

Abstract: A series of Fe, Mn, and Cu doped Ca3Co4O9+δ samples, Ca3(Co,M)4O9+δ (M=Fe, Mn, and Cu), were fabricated by cold high-pressure compacting technique. Their thermoelectric properties were investigated from room temperature up to 1000 K. The cold high-pressure compacting method is advantageous to increasing density and texture, in favor of the improvement of thermoelectric performance. The electrical transport measurements indicate that Fe/Mn substitutes for Co mainly in [CoO2] layers whereas the substitution of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
78
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(90 citation statements)
references
References 55 publications
11
78
1
Order By: Relevance
“…The electrical resistivity of all the samples initially increases with increasing temperature from 300 K up to a certain temperature, then decreases with increasing temperature. Similar results were found for Ca 3 Co 4 O 9 þ δ with the constituent metals partially substituted by other elements [8,23,26]. For temperature below 300 K, the resistivity between T min and T n can be described by ρ=ρ 0 þ AT 2 , where ρ 0 is the residual resistivity owing to the domain boundaries and other temperature-independent scattering mechanisms and A is the Fermi-liquid transport coefficient.…”
Section: Methodssupporting
confidence: 73%
See 1 more Smart Citation
“…The electrical resistivity of all the samples initially increases with increasing temperature from 300 K up to a certain temperature, then decreases with increasing temperature. Similar results were found for Ca 3 Co 4 O 9 þ δ with the constituent metals partially substituted by other elements [8,23,26]. For temperature below 300 K, the resistivity between T min and T n can be described by ρ=ρ 0 þ AT 2 , where ρ 0 is the residual resistivity owing to the domain boundaries and other temperature-independent scattering mechanisms and A is the Fermi-liquid transport coefficient.…”
Section: Methodssupporting
confidence: 73%
“…They have obtained the bulk density of 2.82 g/cm 3 (CS), 4.45 g/cm 3 (HP), 4.59 g/cm 3 (SPS), which corresponds to 60%, 95% and 98% of the theoretical density, respectively. Wang et al [10,23], Pinistoontorn et al [24,25] and Bhaskar et al [3][4][5] also reported that the bulk density of samples is in the range of ca. 3.2-3.8 g/cm 3 for the doped and undoped Ca 3 Co 4 O 9þ δ samples; these values are in the range from 65% to 80% of theoretical density.…”
Section: Methodsmentioning
confidence: 99%
“…2. With the temperature increasing from 300 to 1000 K, the PF of the polycrystalline Ca 3 Co 4 O 9 with different dopants increased [29,[45][46][47]. It can be found that the substitution of transition elements (Fe, Bi, Mn, Ba, Ga) for Ca or Co has a positive effect on the PF improvement of Ca 3 Co 4 O 9 .…”
Section: Ca 3 Co 4 Omentioning
confidence: 91%
“…1 Power factor values of Na x CoO 2 with different dopants as a function of temperature effective dopant which has drastically increased the PF of Ca 3 Co 4 O 9 from 2.3 × 10 −4 to 6.10 × 10 −4 W/mK 2 at 1000 K. Fe ions replace the Co ions in the CoO 2 layers, and this substitution changes the electronic structure and increases the electronic correlations. Thus, doping Fe causes an enhancement in both the Seebeck coefficient and electrical conductivity [46]. On the other hand, doping Cu and Ag decreases the PF value because Cu/Ag ions mainly occupy the sites of Co ions in the Ca 2 CoO 3 layers, which results in an increase of electrical conductivity but a decrease of the Seebeck coefficient.…”
Section: Ca 3 Co 4 Omentioning
confidence: 99%
“…For practical use, their thermoelectric performance must be further improved. One approach is partial substitution for Ca or Co site by metals such as rare earth metals, Ag and transition metal (Nan et al 2003;Wang et al 2008Wang et al , 2010b. Recently, have reported that Ca 3 Co 4 O 9 + δ composite was doped with Lu and Ag by solid-state reaction and sparkplasma-sintering (SPS) techniques.…”
Section: Introductionmentioning
confidence: 99%